2018
DOI: 10.3390/aerospace5020040
|View full text |Cite
|
Sign up to set email alerts
|

Damage Detection in a Composite T-Joint Using Guided Lamb Waves

Abstract: Low velocity impact induces barely visible damage in the form of matrix cracking or delamination that can grow under hydro-thermo-mechanical loading and possibly lead to catastrophic failure if not detected at an early stage. A network of piezoelectric transducers can be used to monitor a structure over time for life prognosis through generation and sensing of guided ultrasonic waves. The aim of this study is to design and develop such a sensing method for damage assessment in a composite T-joint subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The numerical and experimental tests dealing with the wave propagation phenomenon in the isotropic and anisotropic materials confirm the serviceable of this method in the damage detection systems [12,13]. Yu et al demonstrated the effectiveness of the wave propagation analysis in the wood utility poles what proves the versatility and possibility of matching the measurement techniques to the specific subject of analysis [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The numerical and experimental tests dealing with the wave propagation phenomenon in the isotropic and anisotropic materials confirm the serviceable of this method in the damage detection systems [12,13]. Yu et al demonstrated the effectiveness of the wave propagation analysis in the wood utility poles what proves the versatility and possibility of matching the measurement techniques to the specific subject of analysis [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 88%
“…The several measurement techniques in the time domain were developed based on experience with different materials and defects. The pitch-catch method is usually used in the case of the relatively small area of inspection and the multipoint sensor networks [18,19]. The effectiveness of this technique was validated in the structures subjected to static and fatigue loading conditions in coupling with other methods for the damage state assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, numerous SHM methods have been proposed and were successfully tested on simple specimens relevant to aircraft design in laboratory environments [13][14][15][16][17][18]. Recently, scaled demonstrators equipped with multiple sensors have also been built to develop and test the applicability of promising SHM methodologies [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…While laser systems are not embedded in continuous SHM, they are good candidates for contactless inspection, limiting consumption of numerous fixed transducers. [6][7][8][9] Piezoelectric lead zirconate titanate (PZT) transducers are the most commonly used transducers for active SHM, often in pitchcatch configuration, [10][11][12] and able to monitor large and complex CFRP structures, such as a fuselage panel, 13 or wing box. 14 The fundamental anti-symmetric A 0 and symmetric S 0 Lamb wave modes are widely utilized in SHM applications.…”
Section: Introductionmentioning
confidence: 99%